Eutectic hydrated salt phase-change heat storage material with controllable temperature zone as well as preparation method and application of eutectic hydrated salt phase-change heat storage material

By mixing ammonium aluminum sulfate dodecyl and anhydrous sodium sulfate, an eutectic hydrated salt phase change heat storage material with controllable temperature in the temperature zone is solved, and the problem of excessive phase change temperature of existing hydrated salt phase change materials is achieved, and the regulation of phase change temperature and the improvement of material adaptability is achieved.

CN119684974APending Publication Date: 2025-03-25BEIJING UNION UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411583645.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The phase transition temperature of existing hydrated salt phase transition materials is too high to match the outlet temperature limit of commercial electric boilers, and there are problems such as large supercooling, low thermal conductivity and high transportation and storage costs.

Method used

By mixing ammonium aluminum sulfate dodecyl and anhydrous sodium sulfate in proportion, a controllable eutectic hydrated salt phase change heat storage material is prepared, and the phase change temperature is regulated between 75-85℃, which meets the use needs of commercial electric boilers.

Benefits of technology

It realizes effective regulation of phase transition temperature, improves material adaptability, reduces transportation and storage costs, and enhances thermal conductivity and cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684974A_ABST
    Figure CN119684974A_ABST
Patent Text Reader

Abstract

The invention provides a temperature zone controllable eutectic hydrated salt phase change heat storage material and a preparation method and application thereof, and belongs to the technical field of clean heat supply. The temperature zone controllable eutectic hydrated salt phase change heat storage material comprises 85-95 wt% of aluminum ammonium sulfate dodecahydrate and 5-15 wt% of anhydrous sodium sulfate, and the phase change temperature of the phase change heat storage material is 75-85 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of clean heating technology, and in particular, relates to a temperature-zone controllable eutectic hydrated salt phase change thermal storage material, a preparation method and an application thereof, and more specifically, relates to a eutectic hydrated salt phase change material with a phase change temperature of 75-85°C, a preparation method and an application thereof. Background Art

[0002] The development of new energy and renewable clean energy is an inevitable trend to achieve carbon reduction. However, clean energy such as solar energy and wind energy are intermittent and discontinuous, and there are problems such as mismatch between supply and demand in time and space. Therefore, the development of large-scale energy storage technology is crucial. It is reported that thermal energy accounts for about 50% of all energy consumption terminals, so thermal energy storage is an important part. Coupled with wind power or photovoltaics, it plays an important role in the consumption of renewable energy and the construction of new power systems.

[0003] Thermal energy storage technology is a technical means to store the heat of heat sources through heat storage materials and release it at the right time. It is of great significance for large-scale clean heat use, low-carbon heat use, and efficient and rational use of renewable energy. Among them, phase change thermal storage technology uses latent heat to store thermal energy. These materials absorb energy from the surrounding environment during the solid-liquid transformation process, while maintaining the steady-state temperature within the working range of specific thermal applications. As the key core of phase change thermal storage technology, phase change thermal storage materials have the advantages of cyclic repeatability, high energy storage density, smaller system size, and the ability to maintain their temperature in a narrow constant temperature range during operation. Compared with organic phase change materials, inorganic phase change materials are widely available, usually cheaper, and have the advantages of higher heat storage density, higher thermal conductivity, and non-flammability. Therefore, they have broad application prospects in the fields of clean heating, power peak regulation, and industrial waste heat utilization. Ammonium aluminum sulfate dodecahydrate (NH4Al(SO4)2·12H2O) is a typical inorganic hydrated salt phase change material with a phase change temperature of 94°C and a phase change enthalpy value of more than 200 kJ / kg. It is a stable hydrate. During the phase change process, the hydrate composition does not change, and it is a candidate material for building heating and domestic hot water systems. However, commercial heating equipment on the market, such as electric boilers, uses water as the medium, so the maximum outlet water temperature of the boiler should not exceed 85°C. However, the phase change temperature of a single NH4Al(SO4)2·12H2O is too high to match commercial electric boilers, which limits the promotion of hydrated salt phase change materials in heating. At the same time, NH4Al(SO4)2·12H2O has a large degree of supercooling and poor thermal conductivity. At the same time, the material is colorless after melting, so the safety factor of its leakage needs to be considered. Summary of the invention

[0004] In view of this, the present disclosure provides a temperature-controlled eutectic hydrated salt phase change thermal storage material and a preparation method and application thereof, in order to at least partially solve the technical problem. In this regard, the specific technical solution provided by the present disclosure is as follows.

[0005] As a first aspect of the present disclosure, a temperature-zone controllable eutectic hydrated salt phase change heat storage material is provided. In terms of mass percentage, the phase change heat storage material comprises: 85wt%-95wt% of ammonium aluminum sulfate dodecahydrate, 5-15wt% of anhydrous sodium sulfate, and the phase change temperature of the phase change heat storage material is 75-85°C.

[0006] As a second aspect of the present disclosure, a method for preparing a temperature-zone controllable eutectic hydrated salt phase change heat storage material is provided, comprising: adding anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate into a container in proportion, sealing the container, placing the container in a water bath, and heating the container at 95-100° C. for 0.5-1 h; stirring the container when the anhydrous sodium sulfate and the ammonium aluminum sulfate dodecahydrate are half melted, and cooling the container to room temperature to obtain a phase change heat storage material; wherein, in terms of mass percentage, the ammonium aluminum sulfate dodecahydrate is 85-95wt%, and the anhydrous sodium sulfate is 5-15wt%.

[0007] As a third aspect of the present disclosure, there is provided an application of a temperature-zone controllable eutectic hydrated salt phase change heat storage material, wherein the application includes at least one of building wall insulation materials, textile materials, agricultural applications, and clean heating.

[0008] Based on the above technical solution, the temperature-zone controllable eutectic hydrated salt phase change thermal storage material and its preparation method and application provided by the present disclosure have at least one of the following beneficial effects:

[0009] (1) In the embodiments of the present disclosure, it is proposed to use ammonium aluminum sulfate dodecahydrate as the main phase and anhydrous sodium sulfate as the auxiliary phase, and mix them in proportion to obtain a temperature-controlled eutectic hydrated salt phase change heat storage material, and adjust the single phase change temperature of ammonium aluminum sulfate dodecahydrate from 93°C to 75-85°C to achieve the regulation of the phase change temperature. In addition, the eutectic hydrated salt phase change heat storage material provided by the present disclosure has a suitable phase change temperature and a high phase change latent heat, and its compatibility with the highest water outlet temperature (85°C) of electric boilers and heat pumps in the existing market is greatly improved, which solves the contradiction of mismatch with the temperature required by the heating terminal. It can be used as an alternative material for the terminal heating system, which is of great significance to the "peak shifting and valley filling" of the power grid load, and helps to promote the new development of green energy-saving heating.

[0010] (2) In the embodiments of the present disclosure, the main phase and auxiliary phase materials of the present disclosure are general chemicals, which do not require special treatment during transportation and do not require special factory storage, thereby bringing convenience to industrial production and reducing transportation and storage costs.

[0011] (3) In the embodiments of the present disclosure, the method of preparing the temperature-zone controllable eutectic hydrated salt phase change thermal storage material is relatively simple and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a physical comparison diagram of adding different amounts of anhydrous sodium sulfate to form eutectic hydrated salt phase change heat storage materials in the embodiments of the present disclosure;

[0013] Figure 2 This is a diagram of a heat storage test experimental device in an embodiment of the present disclosure;

[0014] Figure 3 is a differential scanning calorimeter (DSC) curve diagram of different phase change heat storage materials in Examples 1-4 of the present disclosure;

[0015] Figure 4 This is an infrared spectrum of the phase change heat storage material in Example 1 of the present disclosure;

[0016] Figure 5 is an X-ray diffraction (XRD) diagram of the phase change heat storage material in Example 1 of the present disclosure;

[0017] Figure 6 The thermal conductivity and front calorific value diagram of the phase change heat storage material prepared at different additive contents in Examples 5-7 of the present disclosure;

[0018] Figure 7 is a cyclic stability diagram of the phase change thermal storage material in Example 5 of the present disclosure;

[0019] Fig. 8A is the XRD pattern of the phase change heat storage material (ASD2) in Comparative Example 1;

[0020] Figure 8B XRD comparison diagram of ASD2 material, ammonium aluminum sulfate dodecahydrate and anhydrous sodium sulfate;

[0021] Fig. 9 It is a schematic diagram of the clean heating system in the embodiment of the present disclosure. DETAILED DESCRIPTION

[0022] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present disclosure. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present disclosure.

[0023] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0024] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).

[0025] At present, the research based on ammonium aluminum sulfate dodecahydrate mainly focuses on how to solve its supercooling, increase thermal conductivity and enhance cycle stability. At present, there is a composite heat storage material prepared from ammonium aluminum sulfate dodecahydrate and hydroxylated graphene, which effectively solves the problem of large supercooling and low thermal conductivity of ammonium aluminum sulfate dodecahydrate, but does not effectively improve the phase change temperature of ammonium aluminum sulfate dodecahydrate. The composite heat storage material composed of ammonium aluminum sulfate dodecahydrate and stearic acid makes the obtained phase change heat storage material have good mechanical properties, but the phase change temperature of the obtained phase change heat storage material is still maintained at about 93°C, which does not meet the outlet water temperature requirements of the terminal heating system, and limits its application. Furthermore, the related technology uses ammonium aluminum sulfate dodecahydrate, Al2O3, and xanthan gum to melt blend, and the obtained phase change heat storage material effectively solves the problems of large supercooling, low thermal conductivity, and poor cycle stability of ammonium aluminum sulfate dodecahydrate. In other words, this method reduces the supercooling of ammonium aluminum sulfate dodecahydrate while increasing its phase change stability.

[0026] However, in the process of implementing the inventive concept of the present disclosure, it was found that the eutectic phase change heat storage material prepared with ammonium aluminum sulfate dodecahydrate as the main phase and sodium sulfate decahydrate as the auxiliary phase can reduce the single phase change temperature of ammonium aluminum sulfate dodecahydrate from a high 93°C to about 85°C. However, because the auxiliary phase is hydrated sodium sulfate, that is, sodium sulfate decahydrate, its phase change temperature is about 30°C, and the phase change temperature point is close to the outdoor ambient temperature in summer, air conditioning refrigeration is required during transportation and storage, otherwise the raw material will change from solid to liquid. The raw material directly changes to liquid, resulting in a significant decrease in the performance of the raw material. Therefore, the use of sodium sulfate decahydrate as the auxiliary phase brings great difficulties to industrial preparation, and the transportation and storage costs are high.

[0027] In response to the above technical problems, the present disclosure provides a temperature-zone controllable eutectic hydrated salt phase change heat storage material with anhydrous sodium sulfate as a secondary phase and ammonium aluminum sulfate dodecahydrate as a primary phase, which solves the problems of current phase change heat storage materials such as large supercooling, low thermal conductivity, instability, poor adaptability of single material phase change temperature zone, and high raw material transportation and storage costs.

[0028] According to the embodiments of the present disclosure, the eutectic system refers to: a plurality of phase change materials are combined to lower the phase change temperature of any phase change material, thereby achieving temperature control of the phase change material.

[0029] Specifically, as the first aspect of the present disclosure, a temperature-zone controllable eutectic hydrated salt phase change heat storage material is provided. In terms of mass percentage, the phase change heat storage material comprises: 85wt%-95wt% of ammonium aluminum sulfate dodecahydrate, 5-15wt% of anhydrous sodium sulfate, and the phase change temperature of the phase change heat storage material is 75-85°C.

[0030] In the embodiments of the present disclosure, in view of the low phase change temperature, high transportation and storage costs of sodium sulfate decahydrate, and the large supercooling, low thermal conductivity and instability of ammonium aluminum sulfate dodecahydrate, the present disclosure proposes to use ammonium aluminum sulfate dodecahydrate as the main phase and anhydrous sodium sulfate as the auxiliary phase, and mix them in proportion to obtain a eutectic hydrated salt phase change heat storage material. By controlling the dosage of anhydrous sodium sulfate to 5-15wt%, on the one hand, it is ensured that the prepared eutectic hydrated salt phase change heat storage material is mixed evenly and does not phase separate, and on the other hand, the single phase change temperature of ammonium aluminum sulfate dodecahydrate can be adjusted from 93°C to 75-85°C to achieve the regulation of phase change temperature. When the dosage of anhydrous sodium sulfate exceeds 15wt%, it is easy to cause uneven mixing of the phase change material and phase separation.

[0031] The auxiliary phase used in this application gives priority to adding compounds containing the same acid radical ions; for chloride salts, because they contain chloride ions, they are corrosive to a certain extent, which is not conducive to the containers used, transportation and storage, and corrosion can easily cause material leakage, so compounds containing sulfate ions are selected. Since all substances exist in ionic form in the eutectic state, the addition of potassium sulfate may cause the composite material to form potassium aluminum sulfate dodecahydrate, and the properties may change, while the addition of anhydrous sodium sulfate will not cause the formation of sodium aluminum sulfate; for barium salts, etc., it is not easy to use due to leakage problems, so anhydrous sodium sulfate with low cost, wide source, low corrosion and stable chemical properties is finally selected as the auxiliary phase. The phase change temperature of anhydrous sodium sulfate is generally above several hundred degrees. After combining with ammonium aluminum sulfate dodecahydrate, it can effectively reduce the phase change temperature of ammonium aluminum sulfate dodecahydrate, and obtain a phase change heat storage material with a phase change temperature of 75-85°C, and it has high stability. The principle of eutectic melting point reduction mainly involves the influence of many factors such as lattice distortion of phase change materials, chemical bond stability, the influence of impurities and lattice bonding force, the composition and characteristics of eutectic mixtures, and the eutectic point and melting process. The eutectic temperature zones of different materials are different.

[0032] According to an embodiment of the present disclosure, the phase change heat storage material further includes an additive, which accounts for 1-5wt% of the total weight of ammonium aluminum sulfate dodecahydrate and anhydrous sodium sulfate. The use of additives can further overcome the problems of large supercooling, low thermal conductivity and poor light absorption capacity of the temperature zone controllable eutectic hydrate salt phase change heat storage material.

[0033] Specifically, the additives used in the embodiments of the present disclosure include: carbon materials with nucleation, high thermal conductivity and light absorption properties, and color indicators for warning material leakage. More specifically, the carbon material includes: at least one of expanded graphite, graphene nanosheets, cellulose nanofibers, and biomass carbon nanotubes. The main purpose of using carbon materials with nucleation properties is to reduce the supercooling of the phase change heat storage material and prevent the theoretical heat release temperature from being maintained at around 75°C during the heat release process when the phase change heat storage material is fully stored. If the supercooling is too large, the phase change heat storage material cannot release heat at this temperature, but needs to release heat at a lower ambient temperature, thereby affecting the controllable release of heat in the system. The addition of carbon materials with high thermal conductivity is to make the heat exchange equipment and the heat storage unit and the heat storage material have a higher heat exchange efficiency, and then require the phase change heat storage material to have a certain thermal conductivity, so it is necessary to add carbon materials with high thermal conductivity. The addition of carbon materials with light absorption properties is mainly to improve the light absorption characteristics of the phase change heat storage material. At present, eutectic hydrated salt phase change heat storage materials are mainly heated by external heat sources, such as heating the phase change materials (i.e., ammonium aluminum sulfate dodecahydrate and anhydrous sodium sulfate) by using boilers to make hot water. In the absence of an external power heat source, it is particularly important to absorb natural sunlight for heating. Therefore, the present disclosure uses carbon materials with light absorption properties to directly use the synthesized phase change heat storage materials to absorb solar radiation energy, convert it into heat energy, and store the heat energy in the phase change heat storage materials, thereby meeting the demand for non-powered heating.

[0034] The color indicator used in the embodiment of the present disclosure has a certain water solubility and does not chemically react with the phase change heat storage material within 100° C. The color indicator used in the present disclosure includes the use of pigments, and the edible pigments include: any one of red yeast rice, chlorophyll, curcumin, carotene, and lemon yellow.

[0035] According to the embodiments of the present disclosure, the latent heat of the phase change heat storage material is 180-280 kJ / kg, the thermal conductivity is 0.5-1.8 W / (m·K), and the heat storage density is 200-205 kJ / kg. The phase change heat storage material provided by the present disclosure has high latent heat and good thermal conductivity.

[0036] According to an embodiment of the present disclosure, the supercooling degree of the phase change heat storage material is 26-32°C.

[0037] According to an embodiment of the present disclosure, a method for preparing a temperature-zone controllable eutectic hydrated salt phase-change heat storage material is provided, comprising: adding anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate into a container in proportion, sealing the container, placing the container in a water bath, and heating the container at 95-100° C. for 0.5-1h; stirring the container when the anhydrous sodium sulfate and the ammonium aluminum sulfate dodecahydrate are half melted, and cooling the container to room temperature to obtain a phase-change heat storage material; wherein, in terms of mass percentage, the ammonium aluminum sulfate dodecahydrate is 85-95wt%, and the anhydrous sodium sulfate is 5-15wt%.

[0038] In an embodiment of the present disclosure, anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate are melted and mixed to obtain a temperature-zone controllable eutectic hydrated salt phase change heat storage material, wherein the raw materials are inexpensive and widely available, the preparation method is relatively simple, and large-scale preparation is possible.

[0039] According to an embodiment of the present disclosure, when half of the anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate are melted, the method further includes: adding an additive and stirring; wherein the amount of the additive added accounts for 1-5wt% of the total weight of the ammonium aluminum sulfate dodecahydrate and the anhydrous sodium sulfate. By adding the additive, the problems of large supercooling, low thermal conductivity and poor light absorption capacity of the temperature-zone controllable eutectic hydrated salt phase change thermal storage material can be further overcome.

[0040] Specifically, the preparation method of the temperature-controlled eutectic hydrated salt phase change thermal storage material includes: pouring anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate into a container, adding a stirrer and sealing, placing the sealed container in a water bath environment (such as a water bath), setting the water bath temperature to 95-100°C, and stirring for 0.5-1h when the anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate phase change materials are half melted, and after the stirring is completed, cooling to room temperature to obtain the temperature-controlled eutectic hydrated salt phase change thermal storage material. Furthermore, when the phase change material is half melted, additives can be added and stirred to obtain a temperature-controlled eutectic hydrated salt phase change thermal storage material containing additives, so as to enhance the thermal conductivity and light absorption performance of the phase change thermal storage material while reducing the degree of supercooling.

[0041] As a third aspect of the present disclosure, a system for preparing a temperature-zone controllable eutectic hydrated salt phase change thermal storage material is provided, comprising: an ammonium aluminum sulfate dodecahydrate storage tank, an anhydrous sodium sulfate storage tank, a mixing tank, a reaction tank, and a transmission channel.

[0042] The ammonium aluminum sulfate dodecahydrate storage tank is used to store the ammonium aluminum sulfate dodecahydrate; the anhydrous sodium sulfate storage tank is used to store the anhydrous sodium sulfate; the mixing tank is connected to the ammonium aluminum sulfate dodecahydrate storage tank and the anhydrous sodium sulfate storage tank through pipelines, and is used to mix the ammonium aluminum sulfate dodecahydrate and the anhydrous sodium sulfate; the reaction tank is provided with a heating unit and a stirring unit, and is used to heat the mixed ammonium aluminum sulfate dodecahydrate and anhydrous sodium sulfate, and the stirring unit is turned on for stirring when the anhydrous sodium sulfate and the ammonium aluminum sulfate dodecahydrate are half melted.

[0043] In the embodiments of the present disclosure, the method and system provided by the present disclosure can realize the automated preparation of temperature-zone controllable eutectic hydrated salt phase change thermal storage materials to achieve industrial large-scale preparation.

[0044] According to an embodiment of the present disclosure, the system further includes: an additive storage tank for storing additives, the additive storage tank being connected to a mixing tank pipeline to transport the additives to the reaction tank for blending.

[0045] Specifically, the industrialized amplification process for preparing a temperature-controlled eutectic hydrated salt phase change heat storage material includes: transporting the ammonium aluminum sulfate dodecahydrate stored in the ammonium aluminum sulfate dodecahydrate storage tank and the anhydrous sodium sulfate stored in the anhydrous sodium sulfate storage tank to a mixing tank through a transmission channel, stirring and mixing in the mixing tank, and transporting the mixed phase change material to a reaction tank through a transmission channel, heating the ammonium aluminum sulfate dodecahydrate and anhydrous sodium sulfate phase change materials through a heating unit in the reaction tank, and when half of the mixture is melted, turning on the stirring unit of the reaction tank to stir the mixture of ammonium aluminum sulfate dodecahydrate and anhydrous sodium sulfate. In the initial stage of stirring, the stirring speed is low (such as 100-200rpm), and as the phase change material gradually melts, the stirring speed is gradually increased (such as 500-800rpm) until it is completely clarified. The heating time of the reaction tank can be 10-20 hours, and the temperature-controlled eutectic hydrated salt phase change heat storage material can be obtained after natural cooling. Furthermore, additives can be added to the clarified solution in the reaction tank, and after sealing, the mixture is stirred evenly for about 1-3 hours. Finally, the evenly mixed solution is discharged and transported to a finished product tank for storage. After the material is cooled, a functional temperature-controlled eutectic hydrated salt phase change thermal storage material can be obtained.

[0046] According to an embodiment of the present disclosure, the present disclosure also provides an application of a temperature-zone controllable eutectic hydrated salt phase change heat storage material, which includes at least one of building wall insulation materials, textile materials, agricultural applications, and clean heating.

[0047] According to an embodiment of the present disclosure, clean heating includes at least one of: heat storage, solar energy, low-grade waste heat utilization, air energy, etc.

[0048] Example

[0049] Example 1

[0050] Preparation of temperature-zone controllable eutectic hydrated salt phase change thermal storage material AS15: Weigh 42.5g of ammonium aluminum sulfate dodecahydrate (AASD) and 7.5g of anhydrous sodium sulfate (SSA, 15wt%) phase change materials, mix them evenly, put them into a reactor, add a magnetic rotor, and seal it. Place it in a constant temperature water bath, set the water bath temperature to 98°C, wait for the phase change material to completely melt into a transparent and clear liquid, turn on the magnetic stirrer and stir for 0.5-1h to make it stir evenly. After completion, wait for it to cool naturally to obtain the eutectic phase change thermal storage material AS15.

[0051] Example 2

[0052] Preparation of temperature-zone controllable eutectic hydrated salt phase change heat storage material AS5: The eutectic phase change heat storage material is prepared by the same method as in Example 1, with the only difference being that only 5 wt % of anhydrous sodium sulfate is added to prepare the eutectic phase change heat storage material AS5.

[0053] Example 3

[0054] Preparation of temperature-zone controllable eutectic hydrated salt phase change heat storage material AS10: The eutectic phase change heat storage material is prepared by the same method as in Example 1, with the only difference being that only 10 wt % of anhydrous sodium sulfate is added to prepare the eutectic phase change heat storage material AS10.

[0055] Example 4

[0056] Preparation of temperature-zone controllable eutectic hydrated salt phase change heat storage material AS20: The eutectic phase change heat storage material is prepared by the same method as in Example 1, with the only difference being that only 20 wt % of anhydrous sodium sulfate is added to prepare the eutectic phase change heat storage material AS20.

[0057] Figure 1 This is a physical comparison diagram of the eutectic hydrated salt phase change heat storage material formed by adding different amounts of anhydrous sodium sulfate in the embodiments of the present disclosure.

[0058] like Figure 1 As shown, when the amount of anhydrous sodium sulfate used is 5-15wt%, the obtained eutectic hydrated salt phase change thermal storage material is mixed evenly and is clear and transparent. When the amount of anhydrous sodium sulfate added exceeds 15wt%, such as 20wt%, the obtained composite material is uneven and has phase separation, so it is preferred to add 5-15wt% of anhydrous sodium sulfate.

[0059] Performance Testing

[0060] The phase change heat storage materials obtained in the above Examples 1-4 were tested by the following testing method, and the specific testing process is as follows.

[0061] (1) The phase change latent heat and phase change temperature of the composite phase change material (i.e., eutectic phase change heat storage material) were tested using a Swiss Mettler Toledo differential scanning calorimeter (DSC). The test temperature range was 25-100°C, the heating rate was 5°C / min, and the crucible containing the phase change heat storage material was sealed without puncturing during the test. The protective atmosphere was N2 with a flow rate of 50 mL / min. The phase change latent heat value and phase change temperature range of the phase change heat storage material can be obtained from the obtained DSC curve.

[0062] (2) The phase change thermal storage material was tested and analyzed using an X-ray diffraction analyzer (XRD standard 1#) from Rigaku Corporation. The test diffraction angle range was 2θ=5°~90°, the scanning speed was 20° / min, and the test step was 0.01°. The crystal structure parameters and phase composition of the phase change thermal storage material can be obtained by comparing the test results with the standard PDF card.

[0063] (3) The infrared spectrum of the phase change thermal storage material was tested using the TENSOR27 Fourier transform infrared spectrometer of Bruker Hong Kong Ltd. The functional groups contained in the compound were determined based on the infrared characteristic absorption peaks in the spectrum, and the structure of the sample was identified by searching the standard spectrum, and the sample was qualitatively and quantitatively analyzed. The test wavelength range is 4000~400cm -1 , resolution 4cm -1 .

[0064] (4) Use a self-made heat storage experimental device to test the heat storage and release capacity of the material in practical applications to obtain its heat storage and release density. Specifically, the heat storage test experimental device is as follows: Figure 2 shown.

[0065] Figure 2 Schematic diagram of the heat storage test experimental device in the embodiment of the present disclosure.

[0066] like Figure 2 As shown, a test unit containing a certain mass of phase change heat storage material is placed in a high-temperature water bath (water bath temperature is 90°C) for heat storage. After the phase change heat storage material stores heat to a preset temperature, the phase change heat storage material is quickly taken out of the water bath and placed in a low-temperature water bath (low-temperature water bath temperature is 40°C) for heat release. When the temperature of the external low-temperature water bath no longer changes, the relevant temperature is recorded. The experiment is repeated 3 times, and the temperature difference is taken as the average value. The heat storage density can be calculated using equations (1) to (3).

[0067] The control group was a test unit without adding phase change heat storage material, and heat storage and heat release tests were carried out.

[0068] (1);

[0069] (2);

[0070] (3);

[0071] Where: —heat storage density of phase change material, kJ / kg; —Mass of stainless steel pipe, kg; — water mass, kg; —Mass of phase change material, kg; —Specific heat capacity of stainless steel pipe, kJ / (kg·K); —Specific heat capacity of water, kJ / (kg·K); —Temperature difference of stainless steel tube containing phase change material, °C; —The stainless steel tube containing phase change material raises the temperature difference of water, ℃; —Temperature difference of stainless steel pipe without phase change material, °C; —Stainless steel pipes without phase change materials cause the water to heat up by a temperature difference of ℃.

[0072] (5) The thermal conductivity of the eutectic composite phase change material was tested using a thermal conductivity meter, Hot Disk 2500s, to obtain its thermal conductivity.

[0073] Figure 3 is a differential scanning calorimeter (DSC) curve diagram of different phase change heat storage materials in Examples 1-4 of the present disclosure, and Table 1 is differential scanning calorimeter (DSC) data of different phase change heat storage materials in Examples 1-4 of the present disclosure.

[0074] Table 1. Differential scanning calorimeter (DSC) data of different phase change thermal storage materials

[0075]

[0076] Combination Figure 3 As shown in Table 1 above, the phase change heat storage material composed of 5-15wt% anhydrous sodium sulfate has a higher latent heat, and there is only one melting peak when only 15wt% anhydrous sodium sulfate is added, indicating that a eutectic mixture is formed. For the addition of 5-10wt% and 20wt% anhydrous sodium sulfate, there are multiple melting peaks, indicating that the phase change heat storage material under this ratio may have other phase change endothermic and exothermic processes. Figure 3 It can be seen that the phase change starting temperature of the temperature-zone controllable eutectic hydrated salt phase change thermal storage material of AS15 is 77.91°C, the phase change peak temperature is 84.79°C, the phase change endpoint temperature is 89.92°C, and the phase change latent heat is 190.97 kJ / kg.

[0077] Figure 4is an infrared spectrum of the phase change heat storage material in Example 1 of the present disclosure, Figure 5 This is an X-ray diffraction (XRD) diagram of the phase change heat storage material in Example 1 of the present disclosure.

[0078] like Figure 4-Figure 5 As shown, the infrared spectrum and X-ray diffraction peaks of the phase change thermal storage material prepared in Example 1 are the same as those of the raw materials (ammonium aluminum sulfate dodecahydrate, anhydrous sodium sulfate), and no other new peaks are generated, confirming that the AS15 eutectic phase change material is a simple physical mixture between NH4Al(SO4)2·12H2O and Na2SO4.

[0079] Example 5

[0080] Preparation of temperature-controlled eutectic hydrated salt phase change thermal storage material AS15E3: Weigh 42.5g of ammonium aluminum sulfate dodecahydrate and 7.5g of anhydrous sodium sulfate (15wt%) phase change material, mix them evenly, put them into the reactor, add the magnetic rotor, seal them, place them in a constant temperature water bath, set the water bath temperature to 95°C, and wait until the phase change material is completely melted into a transparent and clear liquid. Add 3wt% of expanded graphite to the melted solution, seal it, and turn on the magnetic stirrer to stir for 0.5h to stir it evenly. Stir manually for 2min before cooling, and wait for it to cool naturally to obtain the eutectic phase change thermal storage material AS15E3, where E3 means adding 3wt% of expanded graphite.

[0081] Example 6

[0082] The same method as in Example 5 was adopted to add 1 wt % of expanded graphite to prepare the eutectic phase change heat storage material AS15E1.

[0083] Example 7

[0084] The same method as in Example 5 was adopted to add 5 wt % of expanded graphite to prepare the eutectic phase change heat storage material AS15E5.

[0085] Figure 6 Graphs showing thermal conductivity and latent heat values ​​of phase change heat storage materials prepared at different additive contents in Examples 5-7 of the present disclosure.

[0086] like Figure 6 As shown in the figure, when the content of the additive is 3wt%, the thermal conductivity of the prepared phase change thermal storage material is 1.155 W / m·K, which is 116.7% higher than that before addition, and the latent heat value is 182.12 kJ / kg. Further increase of the additive will further increase the thermal conductivity, but the latent heat value will further decrease.

[0087] Figure 7 This is a cyclic stability diagram of the phase change heat storage material in Example 5 of the present disclosure.

[0088] like Figure 7 As shown, in Example 5, the phase change heat storage material has a system supercooling degree that is stable between 26 and 32° C. after 60 heating and cooling cycles, and has good cycle stability.

[0089] Furthermore, the heat storage density of the phase change heat storage material in Example 5 was tested, and it was calculated that the heat storage density of the phase change heat storage material was 204.34 kJ / kg, further indicating that the material has good application potential in the field of heating.

[0090] Comparative Example 1

[0091] The phase change heat storage material (ASD2) was prepared by the same method as in Example 1, except that sodium sulfate decahydrate was used as the auxiliary phase.

[0092] Fig. 8A The XRD diagram of the medium temperature controllable eutectic hydrated salt phase change thermal storage material (ASD2) of comparative example 1 is shown in FIG. Figure 8B This is the XRD comparison diagram of ASD2 material, ammonium aluminum sulfate dodecahydrate and anhydrous sodium sulfate.

[0093] Depend on Figure 8A-B It can be seen that the phase change heat storage material ASD2 formed by the composite of ammonium aluminum sulfate dodecahydrate and sodium sulfate decahydrate will partially lose water and become anhydrous sodium sulfate. Therefore, the phase change heat storage material obtained by XRD test contains both sodium sulfate decahydrate and anhydrous sodium sulfate; while the phase change heat storage phase change material formed by the composite of anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate has a relatively stable property and will not contain part of sodium sulfate decahydrate.

[0094] Furthermore, the phase change heat storage material provided by the present disclosure is suitable for clean heating systems (such as Fig. 9 as shown).

[0095] Fig. 9 It is a schematic diagram of the clean heating system in the embodiment of the present disclosure.

[0096] like Fig. 9 As shown in the figure, a dual storage heating system of valley electricity and phase change heat storage is built to heat the office building rooms in winter. The heat source uses water + phase change heat storage material (PCM) dual storage heating heat source, and the operation of the system is quantitatively analyzed. By calculating the heat release of the heat storage device, the results show that the heat storage and release efficiency of the bottom-in and top-out dual storage heating system is 49.84%, and the actual energy storage density of the phase change heat storage material is calculated to be 205.13kJ / kg, indicating that the heat storage and release effect of the material in actual application is good.

[0097] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.

Claims

1. A temperature-controlled eutectic hydrated salt phase change heat storage material, in terms of mass percentage, comprising: 85wt%-95wt% of ammonium aluminum sulfate dodecahydrate, 5-15wt% of anhydrous sodium sulfate, The phase change temperature of the phase change heat storage material is 75-85°C.

2. The phase change heat storage material according to claim 1, further comprising: The additive accounts for 1-5wt% of the total weight of the ammonium aluminum sulfate dodecahydrate and the anhydrous sodium sulfate.

3. The phase change heat storage material according to claim 2, wherein: The additive includes at least one of a carbon material and a color indicator.

4. The phase change heat storage material according to claim 3, wherein: The carbon material comprises: at least one of expanded graphite, graphene nanosheets, cellulose nanofibers, and biomass carbon nanotubes; The color indicator comprises food pigments, and the food pigments comprise any one of red yeast rice, chlorophyll, curcumin, carotene and tartrazine.

5. The phase change heat storage material according to any one of claims 1 to 4, wherein: The phase change heat storage material has a latent heat of 180-280 kJ / kg, a thermal conductivity of 0.5-1.8 W / (m·K), and a heat storage density of 200-205 kJ / kg.

6. The phase change heat storage material according to claim 1, wherein: The supercooling degree of the phase change heat storage material is 26-32°C.

7. A method for preparing a temperature-controlled eutectic hydrated salt phase-change thermal storage material, comprising: Add anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate into a container in proportion, seal it, place it in a water bath, and heat it at 95-100°C for 0.5-1h; When the anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate are half melted, stirring is performed, and after cooling to room temperature, the phase change heat storage material is obtained; Wherein, in terms of mass percentage, the ammonium aluminum sulfate dodecahydrate is 85-95w%, and the anhydrous sodium sulfate is 5-15wt%.

8. The preparation method according to claim 7, when the anhydrous sodium sulfate and ammonium aluminum sulfate dodecahydrate are half melted, the method further comprises: Add additives and stir; Wherein, the dosage of the additive accounts for 1-5wt% of the total weight of the ammonium aluminum sulfate dodecahydrate and the anhydrous sodium sulfate.

9. Application of the temperature-range controllable eutectic hydrated salt phase change thermal storage material according to any one of claims 1 to 6, wherein: The applications include at least one of building wall insulation materials, textile materials, agricultural applications, and clean heating.

Citation Information

Patent Citations

  • Low-temperature composite phase-change energy storage material and preparation method thereof

    CN112080255A

  • Maleic acid-aluminum ammonium sulfate dodecahydrate / modified expanded graphite composite phase change material and preparation method thereof

    CN117106417A

  • Eutectic phase change material and preparation method thereof

    CN117903755A